PMO-005 Brief intervention reduces future hospital attendance in hazardous alcohol drinkers. (28th May 2012) - Assad-Sangabi, A; Smith, R; Cleminson, J; Jones, L; Elphick, D
Abstract : Introduction: Excessive alcohol consumption is a major health burden facing the NHS. The Fast Alcohol Screening Tool (FAST) is a useful, simple tool to screen for hazardous/harmful drinking. Hazardous drinking is associated with a high risk of psychological or physical problems in the future. In this study, we assess the FAST score in patients attending the Emergency Department (ED) of our hospital. We then evaluate whether brief alcohol intervention on high scorers (hazardous drinkers), in the form of consultation and advice on alcohol related habits, results in fewer future ED attendances. Methods: All those, 18 years and over, attending the ED of Chesterfield Royal Hospital over a 24 h period were asked to take part in this study. All participants were formally consented. Patient demographics were taken, and reason for admission noted. Number of prior ED attendances were noted from hospital records and patient recollection. FAST questionnaires were then filled, followed by a brief intervention [typically lasting 10 min] given to those who scored 3 or above. Investigators had prior training on brief intervention. Frequency of hospital attendance following this episode was then taken from hospital records. Results: 140 patients attended ED, but 25 were excluded (declined participation, life-threatening illness). Therefore, 115 patients participated in the study (60 (52%) female and 55 (48%) male; median age 47). FAST score was 0 in 60 (52%), 1 in 13 (11%), 2 in 19 (17%) and ≥3 in 23 (20%) patients. Brief alcohol intervention was carried out in 19 out of 23 patients who scored ≥3 (not possible in four who were intoxicated with alcohol). These included 9 (48%) female and 10 (52%) male with median age of 39. In this subgroup of patients, 15 had no previous ED attendances, one attended once, one attended twice and two attended three times each in the prior 6 months. Therefore, four out of 19 (21%) of these patients attended ED on a total of nine occasions over that 6 months. 20 out of 92 patients (22%) of those with FAST score <3 had prior admissions over the same period with a total of 25 attendances. Two out of 19 (10%) patients with FAST score ≥3, who were given brief intervention, re-attended over the following 6 months, on one occasion each (total two attendances). 13 out of 92(14%) patients with FAST score <3 re-attended over this time period, with total 17 attendances. Brief intervention therefore appeared to reduce future hospital attendance in hazardous alcohol drinkers. Conclusion: Hazardous alcohol drinkers (with FAST scores ≥3) make up a large proportion of those attending ED. Brief alcohol intervention for these reduces their re-attendance. We therefore recommend front-line ED staff to be trained in brief intervention. Competing interests: None declared.